This is about thermal physics, not a chemical question at all.

If there's no energy lost from the system then,

energy lost by hot substance cooling down = energy gained by cold substance heating up.

Where

mc(T(hot) - T(equilibrium) ) = mc (T(equilibrium) - T(cold))

where

m = mass

c = specific heat capacity

T = temperature

since c are the same

200*(85-x)=150(x-15)

4*(85-x)=3*(x-15)

340-4x=3x-45

then

7x=385

x=55 Celsius

If there's no energy lost from the system then,

energy lost by hot substance cooling down = energy gained by cold substance heating up.

Where

mc(T(hot) - T(equilibrium) ) = mc (T(equilibrium) - T(cold))

where

m = mass

c = specific heat capacity

T = temperature

since c are the same

200*(85-x)=150(x-15)

4*(85-x)=3*(x-15)

340-4x=3x-45

then

7x=385

x=55 Celsius